Cochlear Homocysteine Metabolism at the Crossroad of Nutrition and Sensorineural Hearing Loss - Partearroyo, Teresa; Vallecillo, Néstor; Pajares, María A.; Varela-Moreiras, Gregorio; Varela-Nieto, Isabel (Frontiers in Molecular Neuroscience, 2017)
Hearing loss (HL) is one of the most common causes of disability, affecting 360 million people according to the World Health Organization. HL is most frequently of sensorineural origin, being caused by the irreversible loss of hair cells and/or spiral ganglion neurons. The etiology of sensorineural HL (SNHL) is multifactorial, with genetic and environmental factors such as noise, ototoxic substances and aging playing a role. The nutritional status is central in aging disability, but the interplay between nutrition and SNHL has only recently gained attention. Dietary supplementation could therefore constitute the first step for the prevention and potential repair of hearing damage before it reaches irreversibility. In this context, different epidemiological studies have shown correlations among the nutritional condition, increased total plasma homocysteine (tHcy) and SNHL. Several human genetic rare diseases are also associated with Hcy metabolism and SNHL confirming this potential link. Accordingly, rodent experimental models have provided the molecular basis to understand the observed effects. Thus, increased tHcy levels and vitamin deficiencies, such as folic acid, have been linked with SNHL, whereas long-term dietary supplementation with omega-3 fatty acids improved Hcy metabolism, cell survival and hearing acuity. Furthermore, pharmacological supplementations with the anti-oxidant fumaric acid that targets Hcy metabolism also improved SNHL. Overall these results strongly suggest that cochlear Hcy metabolism is a key player in the onset and progression of SNHL, opening the way for the design of prospective nutritional therapies.